American Contact Dermatitis Society Core Allergen Series: 2020 Update. Issue 5 (September 2020) - Schalock, Peter C.; Dunnick, Cory A.; Nedorost, Susan; Brod, Bruce; Warshaw, Erin; Mowad, Christen; Scheman, Andrew
Abstract : The American Contact Dermatitis Society Core Allergen series was introduced in 2013 and updated in 2017. Changes in our recommended allergens are again necessary, taking into account data from the American Contact Dermatitis Society's Contact Allergen Management Program top 100 allergens from 2018. For the updated series, we removed methyldibromoglutaronitrile and added new haptens: Lyral, Limonene, Linalool, carmine, benzyl salicylate, disperse yellow 3, jasmine, peppermint, pramoxine, shellac, and lauryl polyglucose (glucosides). These additional allergens should increase the yield of relevant positive reactions for our patients.